2020
DOI: 10.3390/cancers12051207
|View full text |Cite
|
Sign up to set email alerts
|

The Proteasome Inhibitor Ixazomib Inhibits the Formation and Growth of Pulmonary and Abdominal Osteosarcoma Metastases in Mice

Abstract: Osteosarcoma is the most common form of primary bone cancer. Over 20% of osteosarcoma patients present with pulmonary metastases at diagnosis, and nearly 70% of these patients fail to respond to treatment. Previous work revealed that human and canine osteosarcoma cell lines are extremely sensitive to the therapeutic proteasome inhibitor bortezomib in vitro. However, bortezomib has proven disappointingly ineffective against solid tumors including sarcomas in animal experiments and clinical trials. Poor tumor pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 73 publications
0
23
0
Order By: Relevance
“…Of note, there was a relatively higher expression of LRRC15 in the osteosarcoma cell line 143B, which is known to be highly metastatic to the lungs of mice following subcutaneous and intramuscular xenotransplantation. [33][34][35] The 143B osteosarcoma cell line is a derivative of the K-Ras oncogene transformed from osteosarcoma cell line HOS-Te85. 34 When comparing in vitro characteristics of these osteosarcoma cell lines, the 143B cell line has the highest rate of proliferation and cell migration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, there was a relatively higher expression of LRRC15 in the osteosarcoma cell line 143B, which is known to be highly metastatic to the lungs of mice following subcutaneous and intramuscular xenotransplantation. [33][34][35] The 143B osteosarcoma cell line is a derivative of the K-Ras oncogene transformed from osteosarcoma cell line HOS-Te85. 34 When comparing in vitro characteristics of these osteosarcoma cell lines, the 143B cell line has the highest rate of proliferation and cell migration.…”
Section: Discussionmentioning
confidence: 99%
“…In our work, we found a differential expression of LRRC15 in osteosarcoma cell lines by western blots and immunofluorescence assays. Of note, there was a relatively higher expression of LRRC15 in the osteosarcoma cell line 143B, which is known to be highly metastatic to the lungs of mice following subcutaneous and intramuscular xenotransplantation 33–35 . The 143B osteosarcoma cell line is a derivative of the K‐Ras oncogene transformed from osteosarcoma cell line HOS‐Te85 34 .…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the inhibition of proteasome function leads to the accumulation of proteins targeted for degradation and subsequent cellular apoptosis (Khan & Stewart, 2011). Previous studies have shown that proteasome inhibitors can induce cell apoptosis in osteosarcoma (Bonvini et al, 2007;Harris et al, 2020;Lu et al, 2008;Patatsos et al, 2018), thereby suggesting that targeting proteasomes may represent a novel therapeutic option for the treatment of osteosarcoma.…”
Section: Introductionmentioning
confidence: 99%
“…This small collection of six original research papers and two review articles in the Special Issue “Rare Childhood Malignancy” highlights the diversity and importance of empirical research into childhood malignancy, a theme that underpins the significant advances that have been made in treating the diseases that constitute cancers in children. These articles cover significant themes in childhood cancer research and include biological studies on the role of MYCN in poor prognosis Wilms’ tumor [ 1 ] and the mTOR complexes in rhabdomyosarcoma [ 2 ]; studies exploring biologically based treatments in ependymoma [ 3 ] and osteosarcoma [ 4 ]; a comprehensive description of a novel orthotopic model for radiation-induced glioma which will be invaluable for preclinical testing [ 5 ]; and two comprehensive review articles on leukemias. One review describes recently identified rearrangements of DUX4 with IGH in childhood B-cell acute lymphoblastic leukemia (ALL) and the diagnostic challenges associated with identifying the rearrangement [ 6 ], and the second proposes that infant acute myeloid leukemia (AML) is a biologically and clinically distinct entity from AML in older children [ 7 ].…”
mentioning
confidence: 99%
“…Validation of this study may lead to better directed therapy for rhabdomyosarcoma. Harris et al [ 4 ] report the exciting finding in preclinical models that the second-generation proteasome inhibitor ixazomib is effective in inhibiting osteosarcoma metastases in athymic mice. When metastatic disease is present in osteosarcoma, the prognosis is poor, with only 20–30% survival.…”
mentioning
confidence: 99%